ANALISIS KONTRIBUSI PENGLAJU/COMMUTER TERHADAP PEMBANGUNAN EKONOMI DI KOTA MEDAN - EVALINA PAKPAHAN; SIMON PATAR RIZKI MANALU (LP2MTBM MAKARIOZ, 2020)
The purpose of this research is to find out the role of the speed/commuting to the economic development of the citycommuter destination of Medan and analyze consumption patterns and multiplier consumption effects in the area of Medan.This type of research is descriptive statistical research using the survey approach. The population is derived from the Mefieldarea to the city of Medan. To obtain the sample amount is used secondary data published by the central Statistic Agencywhile the primary data uses a questionnaire instrument. The results of the research on the factors affecting the commuterwork in the city of Medan, among others, close to the city of Medan, easy and affordable transportation (just by usingmotorcycles and public transportation), there is no work in the home area, and want to work with high income. The pattern ofcommuter labor consumption in the city of Medan is food consumption and not food. Consumption is not a food greater thanfood consumption. Large number of commuter consumption multipliers of 1.43. The definition of the value of this multiplier isif there is a change or addition of one rupiah for commuter consumption then there is an increase in the output in theeconomy of Medan city as the value of multipliers.